Building Students' Social Caring Character Through an Attitude of Belonging - Rofiq, Ahmad Ainur; Ali, M. Makhrus; Aziz, Rahmad (Universitas Muhammadiyah Magelang, 2024)
Education has an important role in building the socially caring character of students. The sense of belonging has a strategic role in developing it. This study aims to determine the influence of a sense of belonging on students' social concern character. The research subjects were 225 students, chosen randomly from two high schools in Kediri Regency and Malang Regency, East Java. Data were collected through the school climate scale and social concern scale. Analysis was conducted using simple regression techniques. The analysis shows that there is an influence of school climate on students' socially caring character (R = 413 p < 0.010). Sense of belonging is the most dominant indicator influencing students' social awareness (β=.201<.010). The results of this study suggest that building students' social awareness can be done by instilling a sense of belonging in students.